Atomically dispersed nickel species in a two-dimensional molecular sieve: Origin of high activity and stability in dry reforming of methane - Min, Hyung Ki; Kweon, Sungjoon; Kim, Young Woo; An, Hyejin; Jo, Donghui; Park, Eun Duck; Shin, Chae Ho; Park, Min Bum (Applied Catalysis B: Environmental, 2021)
Two-dimensional (2D) molecular sieves with highly dispersed nickel species are attractive catalysts for the dry reforming of methane (DRM) because of the ease of molecular diffusion and the deactivation resistance by coke deposition. Here we report the single-step preparation of a 2D nickel silicate molecular sieve with delaminated MWW layers (Ni-DML) by the simple hydrothermal conversion of a borosilicate MWW precursor with nickel nitrate solution. More than 20 wt.% of nickel species were well dispersed in the framework of Ni-DML and the lowest stabilization energy of nickel cluster was calculated using density functional theory calculations. Ni-DML exhibited extremely high conversions of CH4 and CO2 as well as an extraordinary stability, maintaining its activity for 10 days on stream due to the in-situ formation of metallic nickel clusters from the framework species. Ni-DML can be used as a catalyst for DRM without pretreatments such as air calcination and H2 reduction.
Keywords: Coke deposition; Dry reforming-of-methane; High activity; Layered zeolite; Molecular diffusion; MWW; Nickel clusters; Nickel species; Two-dimensional; ]+ catalyst; Delamination; Dry reforming of methane; Layered zeolite; MWW; Nickel